2017
DOI: 10.1002/pssa.201700633
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Plasma‐Damaged‐Layer Removal on GaN HEMT Devices

Abstract: Plasma‐damage during the dry‐etch process often induces degradation of the electric performance in GaN high electron mobility transistor (HEMT) devices. In this paper, the effects of wet‐etch processing on plasma‐damaged AlGaN films using various chemical solutions and propose the best chemical formulation are reported. Three chemical solutions are selected by a combinatorial method. A MIS‐capacitor TEG is fabricated on an AlGaN/GaN structure, and each surface is evaluated by XPS, SIMS, TEM, and AFM. From the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…With the after RIE sample, a 2-3-nm-thick amorphous layer was observed at the surface of the AlGaN film. Since we have already confirmed a high concentration of oxygen at the surface of this sample 30,31) from prior X-ray photoelectron spectroscopy (XPS) measurements, this amorphous layer is thought to be an oxidized layer. Applying the 2D FFT sampling Moiré method, we confirmed that more than 200 defects were clearly observed along the amorphous= AlGaN boundary.…”
Section: Moiré Phase Analysismentioning
confidence: 61%
See 2 more Smart Citations
“…With the after RIE sample, a 2-3-nm-thick amorphous layer was observed at the surface of the AlGaN film. Since we have already confirmed a high concentration of oxygen at the surface of this sample 30,31) from prior X-ray photoelectron spectroscopy (XPS) measurements, this amorphous layer is thought to be an oxidized layer. Applying the 2D FFT sampling Moiré method, we confirmed that more than 200 defects were clearly observed along the amorphous= AlGaN boundary.…”
Section: Moiré Phase Analysismentioning
confidence: 61%
“…This chemical formulation was carefully selected among numerous chemical candidates using a combinatorial method and also confirmed to be effective for removal of the plasmadamaged layer. 30,31) All processes including epitaxy growth, plasma etching, and oxygen ashing were performed with commercially available equipment. As for the patterned samples assuming a GaN MOSFET structure, the AlGaN=GaN heterostructure grown on a Si substrate was prepared, and afterward recessed by ICP-RIE.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The dry etching rate can reach to the level of micron per minute handily [55,56]. However, many factors need to be considered to evaluate the dry etching quality of GaN and AlGaN, such as the surface morphology, sidewall profile, etching anisotropy, material selectivity, material damage, etching uniformity and so forth.…”
Section: Mesa Etchingmentioning
confidence: 99%